(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
The Badge Sandpit was a hands-on, exploratory initiative designed to help educators, learning designers, and workforce professionals move beyond the theory of digital credentials and begin experiencing them in practice. Running from November 17 to December 10, 2025, the Badge Sandpit was a virtual, challenge-based event in which participants completed short, practical activities designed to build familiarity and confidence with digital credentials, platforms, and recognition tools. Challenges included claiming badges, designing them, exploring Rich Skill Descriptors, testing Learning, and Employment Records, and experimenting with Artificial Intelligence-powered skills tools. The format was intentionally low pressure and flexible, allowing participants to engage at their own pace while producing tangible outcomes in the form of digital badges and reflective insights. This poster presentation introduced the design and intent of the Badge Sandpit, including the challenge model, platform engagement strategy, and overall learner experience. The initiative was inspired by the hands-on exploration space at the 2025 Badge Summit, where participants could try multiple credentialing platforms in a comparative and playful way. The Sandpit translated that spirit into a virtual and globally accessible format. Participants accessed the experience through a dedicated Substack site, where content was delivered via email and archived for flexible engagement. The site hosted weekly challenges co-designed with platform providers, reflective prompts, and community discussions, invitations to live webinars and question-and-answer sessions, and a final showcase webinar on December 10 to highlight key learnings and participant stories. The Sandpit was hosted by Lifelong Learning Practice and supported by the Australasian Microcredential Network. It also received in-kind support and visibility from CredX, Micro-credential Multiverse, the Badge Summit, and Micro-credential Polska. Each platform partner contributed a challenge that enabled participants to engage with their tools in a practical, learner-centered way. The poster outlined the rationale for a challenge-based credentialing event, described the learner journey across three weeks, previewed example challenges, and reflected on how playful, hands-on models can shift perceptions and build capability across the recognition Ecosystem. The Badge Sandpit avoided lectures, demonstrations, and static content. Instead, it focused on learning through experimentation, reflection, and peer connection. It was particularly suited to those working in the complex middle space of digital credentials wanting to explore them meaningfully. The poster also served as a call to action, inviting ePIC attendees to participate, promote the event, or contribute a challenge. Whether new to digital recognition or building systems at scale, participants were invited to test, explore, and grow together. Keywords: digital credentials, microcredentials, badge design, exploration, sandbox